2010
DOI: 10.1002/ajmg.a.33552
|View full text |Cite
|
Sign up to set email alerts
|

Autosomal dominant syndrome of camptodactyly, clinodactyly, syndactyly, and bifid toes

Abstract: We report on a 25-year follow-up of a Pakistani kindred with a unique combination of camptodactyly and clinodactyly of 5th fingers, mesoaxial camptodactyly of toes, and ulnar deviation of 3rd fingers. The less common anomalies in the affected subjects include syndactyly involving all digits, and bifid toes. This condition is grossly bilateral, symmetrical, and affects upper and lower limbs of the 26 affected subjects in the kindred. The comparable number of affected male and female subjects (chi(2) = 0.154, P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…They both may be sporadic or familial 1,2,5,6,8 . In inherited forms of Kirner's deformity, it is an independent anomaly, but it can also occur as a minor part of different syndromes such as Down syndrome, pes cavus, osteomyelitis, and progressive myositis ossificans .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They both may be sporadic or familial 1,2,5,6,8 . In inherited forms of Kirner's deformity, it is an independent anomaly, but it can also occur as a minor part of different syndromes such as Down syndrome, pes cavus, osteomyelitis, and progressive myositis ossificans .…”
Section: Discussionmentioning
confidence: 99%
“…In severe forms, flexion contractions are usually seen in multiple digits of both hands and this form is associated with other congenital anomalies such as chromosomal disorders, craniofacial diseases and skeletal deformities 5 . In isolated camptodactyly, one or both little fingers are affected and this form is inherited in autosomal dominant trait with variable penetrance or expressivity, or it may be sporadic 5,6 . Knuckle pads upon the PIP joints might also be observed in combination with isolated camptodactyly 7 .…”
Section: Introductionmentioning
confidence: 99%
“…3 One in every 2000-3000 live births has a syndactyly or webbed finger, which is the most common congenital anomaly. 4 Males are twice as likely as females to suffer from this condition, which accounts for 20% of all hand deformities. 50% of the time, there are bilateral syndactylies.…”
Section: Introductionmentioning
confidence: 99%
“…II -pre-adolescence (acquired): developing normally between 7-11 years of age, progressive form which may transform into a severe deformity of up to 90°; it affects girls more often than boys; III -associated with a variety of syndromes (syndromic camptodactyly): involves multiple digits of both extremities, severe deformity which occurs in conjunction with craniofacial disorders (orofacialdigital syndrome, craniocarpotarsal dystrophy, oculodentaldigital dysplasia), chromosomal disorders (trisomy 13-15), short stature (mucopolysaccharidosis, camptomelic dysplasia, facial-digital-genital syndrome), and other syndromes (Zellweger syndrome, blau syndrome, Tel Hashomer camptodactyly syndrome, Jacobsen syndrome, Weaver syndrome and many more) [3,[5][6][7].…”
mentioning
confidence: 99%
“…camptodactyly may develop as a part of over 150 hereditary syndromes [7,8]. In medical practice there are sometimes cases observed that do not fall into these 3 categories [9,10].…”
mentioning
confidence: 99%